Recent Advances in Asymmetric Reactions Catalyzed by Proline and Its Derivatives - Liu, Jie; Wang, Lei (Synthesis, 2017)
Asymmetric reactions are carried out by organocatalysis in many ways, making them very competitive and practical. One remarkable molecule, the amino acid proline, has become a crucial component in organocatalysis because of its ability to promote chemical transformations with high enantioselectivity. The following review discusses the contributions and recent advances in the field of asymmetric reactions catalyzed by l-proline and its derivatives.1 Introduction2 Asymmetric Aldol Reactions Catalyzed by Proline and Its Derivatives2.1 Reactions of Ketones as Aldol Donors with Aldehydes as Aldol Acceptors2.2 Reactions of Aldehydes as Aldol Donors with Aldehydes as Aldol Acceptors2.3 Reactions of Aldehydes as Aldol Donors with Active Ketones as Aldol Acceptors2.4 Reactions of Ketones as Aldol Donors with Active Ketones as Aldol Acceptors3 Asymmetric Mannich Reactions Catalyzed by Proline and Its Derivatives4 Asymmetric Michael Reactions Catalyzed by Proline and Its Derivatives5 Asymmetric α-Amination Reactions Catalyzed by Proline and Its Derivatives6 Conclusion
Keywords: proline; aldol reaction; Mannich reaction; Michael reaction; α-amination reaction